Major Depression in Chinese Medicine Outpatients with Stagnation Syndrome: Prevalence and the Impairments in Well-Being - Ng, Siu-Man (Evid Based Complement Alternat Med, 2018)
Stagnation syndrome, a diagnostic entity in traditional Chinese medicine (TCM), has been long regarded as the TCM counterpart of major depression in Western medicine. The study investigated the prevalence of major depression among stagnation syndrome patients and evaluated their well-being and functioning outcomes. In total, 117 patients diagnosed with stagnation syndrome were measured using Stagnation Scale, the Patient Health Questionnaire-9 (PHQ-9), and the Body-Mind-Spirit Well-Being Inventory. Results indicate major depression among stagnation syndrome patients was characterized by a high co-occurrence rate and worse physical, mental, and functional outcomes. More than one-quarter (26.5%) of the patients met the DSM-V diagnostic criteria for major depression and over half (53%) exceeded the PHQ-9 cutoff (score above 10) for moderate/severe depression symptoms. The wellness of the stagnation syndrome patients was worse (M = 298.2, SD = 66.5) than that of the general population (M = 360.9, SD = 79.9), with a large Cohen's d value of 0.9. The “wellness outlook” of the depressed stagnation syndrome patients appeared grimmer (M = 252.3, SD = 52.2). The correlation between stagnation and depression was higher for affective symptoms than somatic symptoms. Physical distress did not mediate the relationship between stagnation and daily functioning. These might suggest that stagnation syndrome and major depression may share some similar psychological mechanisms.